PKM – Peningkatan Kemampuan Dosen Dalam Menyusun Manuskrip Penelitian Melalui Workshop Rekonstruksi Hasil Analisis Data Untuk Dosen AMIK Serang - Tb Ai Munandar; Ajif Yunizar Pratama Yusuf; Tyastuti Sri Lestari; Ahmad Dedi Jubaedi; Harsiti Harsiti; Agus Setyawan (Jurnal Dharmabakti Nagri, 2023)
As a lecturer, the ability to compile research manuscripts is a crucial skill to possess. However, there are still a significant number of junior and senior professors who frequently struggle with writing research papers. There are also many professors who are able to analyse data, but they struggle when it is time to incorporate it into manuscripts. This community service activity aims to assist lecturers in putting together research paper draughts, particularly for community service partners. In general, this activity can be divided into two distinct phases: preparation and implementation. Beginning preparatory activities include the identification of partners' problems and requirements, the creation of activity schedules, and ongoing dialogue between the service team and partners. This is done to level the perception of the carried out activities. Following the completion of the preparatory phase, the implementation of community service occurs. During the implementation phase, participants received training from two instructors using distinct materials. This community service activity uses workshops and resource sharing as its methodology. Before and after the activity, pre- and post-test questionnaires were distributed in order to assess the participants' understanding and knowledge. Community service activities have a significant effect on participants' comprehension when composing research paper draughts, as demonstrated by the findings. 67% of the participants who took the post-test indicated that they comprehended the preparation of research manuscripts based on the results of the data analysis. 33% of the remaining respondents indicated that they did not understand.